Macrophage- and pluripotent-like reparative Muse cells are unique endogenous stem cells distinct from other somatic stem cells - Dezawa, Mari (Frontiers in Bioengineering and Biotechnology, 2025)
Muse cells are endogenous reparative stem cells with dual characteristics: pluripotent-like and macrophage-like. They can be identified by the pluripotent surface marker stage-specific embryonic antigen-3-positive (SSEA-3 (+)) cells in the bone marrow, peripheral blood, and various organs, including the umbilical cord and amnion. Muse cells can differentiate into ectodermal, endodermal, and mesodermal lineage cells, self-renew, and selectively migrate to damaged sites by sensing one of the universal tissue damage signals, sphingosine-1-phosphate (S1P). At these sites, they phagocytose damaged/apoptotic cells and differentiate into the same cell type as the phagocytosed cells. In this manner, Muse cells replace damaged/apoptotic cells with healthy, functioning cells, thereby repairing tissues. Due to their specific immunosuppressive and immunotolerant mechanism, clinical trials have been conducted for acute myocardial infarction (AMI), subacute ischemic stroke, epidermolysis bullosa, amyotrophic lateral sclerosis (ALS), cervical spinal cord injury, neonatal hypoxic-ischemic encephalopathy (HIE), and COVID-19 acute respiratory distress syndrome. These trials involved the intravenous injection of ∼1.5 × 107 donor Muse cells without human leukocyte antigen (HLA) matching or immunosuppressant treatment, and they demonstrated safety and therapeutic efficacy. Thus, donor Muse cell treatment does not require gene manipulation, differentiation induction, or surgical intervention. These unique characteristics distinguish Muse cells from other somatic stem cells, such as mesenchymal stem cells, VSEL stem cells, and marrow-isolated adult multi-lineage inducible (MIAMI) cells.